2022
DOI: 10.3390/bs12120493
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions, Measures, and Contexts in Psychological Investigations of Curiosity: A Scoping Review

Abstract: The study of curiosity as a construct has led to many conceptualisations, comprising of different dimensions. Due to this, various scales of curiosity have also been developed. Moreover, some researchers have conceived of curiosity as a general trait-like, while others have included contexts, such as the workplace, or education when investigating curiosity. This scoping review aims to scope the extant psychological literature on curiosity in order to better understand how it has been studied, specifically with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…The validation of the Curiosity and Exploration Inventory-II with a sample of Chinese university students did not support the original two-factor structure, but instead suggested that the instrument had a single-factor structure (Ye et al, 2015). Given the emphasis on collectivism and stress tolerance in Chinese culture (Yow et al, 2022), Chinese children may face more pressure to come out of their comfort zone to become curious and insist guring out their confusions. So they may tend to ask fewer questions and prefer independent exploration.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The validation of the Curiosity and Exploration Inventory-II with a sample of Chinese university students did not support the original two-factor structure, but instead suggested that the instrument had a single-factor structure (Ye et al, 2015). Given the emphasis on collectivism and stress tolerance in Chinese culture (Yow et al, 2022), Chinese children may face more pressure to come out of their comfort zone to become curious and insist guring out their confusions. So they may tend to ask fewer questions and prefer independent exploration.…”
Section: Introductionmentioning
confidence: 93%
“…Curiosity is the innate and universal desire to seek out new information and experiences to close a gap in knowledge (Jirout et al, 2022;Jirout & Klahr, 2012), and it is considered by psychologists, philosophers, and physicists to be a vital aspect of personality (Yow et al, 2022;Zurn & Bassett, 2018). De ned as an adaptive attraction to novel stimulus which facilitated survival (Spielberger & Reheiser, 2009), curiosity also helped people cope with potential risks by accumulating novel experience with non-instant feedback and was believed to enhance well-being(Lydon-Staley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Also from a psychological perspective curiosity is an intriguing phenomenon because individuals are intrinsically interested in issues which are very important not only for them but also for future generations. 16 , 17 Curiosity is an intrinsic need to seek out new information and sensory experiences. It motivates exploratory behaviour.…”
Section: Introductionmentioning
confidence: 99%